Preparation and Characterization of Genipin-Crosslinked Chitosan/Poly(ethylene glycol) Composites Films - Liu, Yangshuo; Yu, Fucheng (Asian Journal of Chemistry, 2012)
Chitosan/poly(ethylene glycol) interpenetrating networks were prepared using solution casting technique. A naturally occurring and nontoxic cross-linking agent, genipin, was used to form the genipin-crosslinked chitosan and chitosan/poly(ethylene glycol) blends networks, where four types of poly(ethylene glycol) were used. Genipin overcomes the problem of physiological toxicity inherent in the use of some common synthetic chemicals as cross-linking agents. It was shown that the properties of films made by blending chitosan with four types of poly(ethylene glycol). The swelling ratio increase with the increase of molecule weight of poly(ethylene glycol). The mechanical properties were slightly improved with the proper amount of molecule weight of poly(ethylene glycol). The surface properties of the films were also examined by contact angles. The results showed that in water, the cross-linked chitosan and chitosan/poly(ethylene glycol) blends were more hydrophobic with the decrease of the molecular weight of poly(ethylene glycol).